"The Rebound Effect", Do improvements in energy efficiency lead to economy-wide reduction in energy consumption? - Stastny, Martin; Koten, Silvester van, 1970-; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
Improving energy efficiency is considered to be one of the means to successfully reduce energy consumption. At the same time improving energy efficiency implies that the real price for energy services will decrease and as a result will stimulate energy consumption whereas savings associated with higher energy efficiency will be partially diminished. This paradox is better known as the rebound effect. Additionally to a detailed definition of the direct rebound effect, this thesis establishes on the basis of existing researches that the price elasticity of demand for energy services plays a major role in terms of the extent of the rebound effect. Based on the triggers for the rebound effect, applicable policies are proposed and analyzed which can soften rebound effects - such as carbon tax, cap and trade system and standards and regulations. In this context most policies aim to increase the real price of energy services. This thesis concludes both that the existing energy efficiency policies are not adequately pursued and that energy efficiency technology should be fostered since it will also weaken rebound effects.
Vedoucí práce: Silvester van Koten
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses